Acquisition of Key Vacuum-Assisted Resin Transfer Molding Parameters through Reverse Scanning for Application in the Manufacturing of Large Fiber-Reinforced-Plastic Products - Guang-Min Luo; Kai-Lin Chen; Chen-Ting Hsu (International Journal of Polymer Science)
Software-based mold flow analysis is often performed to confirm optimized resin pipe arrangements. In this study, the GeoDict software and reverse scanning were employed to develop a method for performing rapid porosity and permeability estimation. A comparison of the results from one-dimensional resin flow and Easyperm tests revealed a 10% variation in the porosity and permeability parameters obtained through the proposed rapid estimation method. In addition, the obtained parameters were substituted into a Moldex3D model to simulate the resin flow on the personal watercraft hull during vacuum-assisted resin transfer molding (VARTM). A comparison of simulation results and hull infusion results revealed that the integration of the proposed rapid estimation method with Moldex3D allowed for the accurate simulation of the resin flow in large fiber-reinforced-plastic (FRP) products (variation <8%). The proposed method can be applied to large wind turbine FRP parts and large FRP yacht components to increase process planning efficiency and product stability.